2023
DOI: 10.5414/alx02382e
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Severe chronic spontaneous urticaria successfully treated with omalizumab and dupilumab

Abstract: Urticaria is a disease triggered by mast cells and characterized by recurrent symptoms such as wheals and/or angioedema. Most patients benefit from treatment with antihistamines (AH) or, if not effective enough, from additional therapy with omalizumab, which leads to significant symptom relief. Here we present a patient with therapy-resistant chronic spontaneous urticaria treated with AH, omalizumab, and glucocorticosteroids. The subsequent recommended therapy according to the current guideline, cyclosporine A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Chronic spontaneous urticaria (CSU) entails the absence of identified causes of urticaria and can be highly debilitating and recalcitrant to standard treatments. A total of 14 patients were reported that had failed standard therapies with antihistamines, omalizumab and/or ciclosporin and were subsequently treated with dupilumab (12/14) or a combination of dupilumab and omalizumab (2/14) ( Table 5 ) [ 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ]. Complete sustained resolutions were reported in 10/14 patients by clinical evaluation and the 7-day urticaria activity score (UAS7) or urticaria control test (UCT); a UAS7 of 0 was reported in 5 of these cases.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic spontaneous urticaria (CSU) entails the absence of identified causes of urticaria and can be highly debilitating and recalcitrant to standard treatments. A total of 14 patients were reported that had failed standard therapies with antihistamines, omalizumab and/or ciclosporin and were subsequently treated with dupilumab (12/14) or a combination of dupilumab and omalizumab (2/14) ( Table 5 ) [ 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ]. Complete sustained resolutions were reported in 10/14 patients by clinical evaluation and the 7-day urticaria activity score (UAS7) or urticaria control test (UCT); a UAS7 of 0 was reported in 5 of these cases.…”
Section: Resultsmentioning
confidence: 99%